1997
DOI: 10.1002/(sici)1096-9861(19971110)388:1<89::aid-cne6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase in the adult and developing thalamus: Histochemical and immunohistochemical study in the rat

Abstract: The distribution of neuronal elements that express nitric oxide synthase (NOS), the synthetic enzyme of the free radical nitric oxide, was investigated in the adult and developing rat thalamus by means of NADPH-diaphorase (NADPH-d) histochemistry, which is a marker of NOS. Immunocytochemistry was also used to confirm the equivalence between the histochemical pattern of staining and the distribution of the expression of the neuronal NOS isoform. In the adult thalamus, NADPH-d-positive and NOS-immunoreactive per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The present report extends the descriptions of the topography of NOS-positive neuronal elements in the thalamus (Mitrofanis 1992;Vincent and Kimura 1992;Gabbott and Bacon 1994;Rodrigo et al 1994;Sugaya and McKinney 1994;Bertini and Bentivoglio 1997;Kharazia et al 1997). In addition to the comprehensively described NOS-containing cell territories (Bertini and Bentivoglio 1997), we add the subparafascicular nucleus.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The present report extends the descriptions of the topography of NOS-positive neuronal elements in the thalamus (Mitrofanis 1992;Vincent and Kimura 1992;Gabbott and Bacon 1994;Rodrigo et al 1994;Sugaya and McKinney 1994;Bertini and Bentivoglio 1997;Kharazia et al 1997). In addition to the comprehensively described NOS-containing cell territories (Bertini and Bentivoglio 1997), we add the subparafascicular nucleus.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to the comprehensively described NOS-containing cell territories (Bertini and Bentivoglio 1997), we add the subparafascicular nucleus. We confirm previous reports showing that the main thalamic relay nuclei in the rat lack a significant population of NOS-positive perikarya.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed that the level of NADPHd was higher than that of MGv and MGd. Finally, positive NADPHd cells were seen in these nuclei, but not in MGv or MGd (Druga and Syka, 1993;Bertini and Bentivoglio, 1997). Our study points out that two areas could be differentiated in the PL: a dorsal area composed of the MGm and PIN, that can only be differentiated from cell density; and a ventral area composed of the PP plus the SPFL, that also showed significant differences in cell density.…”
Section: Parcellation and Functional Significance Of Plmentioning
confidence: 57%
“…1 in Weinberg et al 1996a). Mappings of the CNS distribution of NADPHd/NOS (Vincent et al 1983a, b;Mizukawa et al 1989;Valtschanoff et al 1992Valtschanoff et al , 1993aVincent and Kimura 1992;Geula et al 1993;Johnson and Ma 1993;Onstott et al 1993;Egberongbe et al 1994;Rodrigo et al 1994Rodrigo et al , 2006Vizzard et al 1994;Blottner et al 1995;Leonard et al 1995;Satoh et al 1995;Sobreviela and Mufson 1995;Vincent 1995;Bertini and Bentivoglio 1997;Bidmon et al 1997;Kharazia et al 1997;Iwase et al 1998;Oerman et al 1998;Downen et al 1999;Paxinos et al 1999;Usunoff et al 1999Usunoff et al , 2003Lazarov 2002;Garbossa et al 2005;Gotti et al 2005) consistently show that this enzyme appears in groups of neurons that cannot be defined by other anatomical criteria (perikaryal size, somatodendritic morphology, neuronal connectivity, etc.). NOSpositive neurons are to be found throughout the neuraxis, from the cerebral cortex to the spinal cord, as well as in the sensory and autonomic ganglia.…”
Section: Introductionmentioning
confidence: 99%